2012
DOI: 10.1093/jxb/ers227
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a putative Arabidopsis BAHD acyltransferase causes dwarfism that can be rescued by brassinosteroid

Abstract: Plant growth and development are ensured through networks of complex regulatory schemes. Genetic approaches have been invaluable in dissecting these regulatory pathways. This study reports the isolation of a semi-dominant dwarf mutant designated abnormal shoot1-1 dominant (abs1-1D) through an Arabidopsis T-DNA activation tagging mutant screen. It was shown that the overexpression of a novel BAHD family acyltransferase gene, ABS1/At4g15400, was the cause of the dwarf phenotype in abs1-1D. Overexpression of ABS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Recently, two additional enzymes, namely BRASSINOS-TEROID INACTIVATOR 1 (BIA1)/ABNORMAL SHOOT1 (ABS1) and BR-RELATED ACTYLTRANSFERASE1 (BAT1)/PIZZA (PIZ) that were characterized as putative acyltransferases, were shown to modulate BR levels in Arabidopsis (Choi et al, 2012;Roh et al, 2012;Schneider et al, 2012;Wang et al, 2012a). Results of in vivo feeding and in vitro biochemical assays suggest that BRI1-5 ENHANCED1 (BEN1), an Arabidopsis gene encoding a dihydroflavonol 4-reductase (DFR)-like protein, an enzyme presumably involved in the flavonoid pathway, is also involved in BR inactivation (Yuan et al, 2007).…”
Section: Br Inactivationmentioning
confidence: 99%
“…Recently, two additional enzymes, namely BRASSINOS-TEROID INACTIVATOR 1 (BIA1)/ABNORMAL SHOOT1 (ABS1) and BR-RELATED ACTYLTRANSFERASE1 (BAT1)/PIZZA (PIZ) that were characterized as putative acyltransferases, were shown to modulate BR levels in Arabidopsis (Choi et al, 2012;Roh et al, 2012;Schneider et al, 2012;Wang et al, 2012a). Results of in vivo feeding and in vitro biochemical assays suggest that BRI1-5 ENHANCED1 (BEN1), an Arabidopsis gene encoding a dihydroflavonol 4-reductase (DFR)-like protein, an enzyme presumably involved in the flavonoid pathway, is also involved in BR inactivation (Yuan et al, 2007).…”
Section: Br Inactivationmentioning
confidence: 99%
“…BR inactivation can be achieved via multiple approaches in Arabidopsis , including hydroxylation (Neff et al ., 1999; Turk et al ., 2003), glycosylation (Poppenberger et al ., 2005; Husar et al , 2011), acylation (Roh et al ., 2012; Wang et al ., 2012a; Schneider et al ., 2012b; Zhu et al ., 2013b; Choi et al ., 2013; Zhang and Xu, 2018), and other unknown or unconfirmed mechanisms (Turk et al ., 2005; Takahashi et al ., 2005; Nakamura et al ., 2005; Yuan et al ., 2007; Marsolais et al ., 2007; Thornton et al ., 2010; Sandhu and Neff, 2013). At least ten BR-inactivating genes have been identified in Arabidopsis including; P450 hydroxylases, glycosyltransferases, acyltransferases, sulfotransferases and a reductase.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the enzyme responsible for phosphorylation of BR, namely BR kinase, is likely specific for CS in both plants. In Arabidopsis thaliana, several genes involved in BR conjugation, such as UGT73C5 and UGT73C6 for glucosylation (Poppenberger et al 2005, Husar et al 2011, ST4 and ST1 for sulfonation (Marsolais et al 2007) and BAHD and BAT1/DRL1/PIZZA for acylation (Roh et al 2012, Schneider et al 2012, Wang et al 2012, Choi et al 2013, Zhu et al 2013, have been identified. Overexpression of these genes altered the endogenous levels of BRs, most likely due to the reduction of the amounts of CS and BL, and exhibited abnormal growth and development, which was observed in BR-deficient Arabidopsis mutants.…”
Section: Discussionmentioning
confidence: 99%